Transfer of T cells from intranasal ovalbumin-immunized mice ameliorates allergic response in ova-sensitized recipient mice - AKKOÇ, TUNÇ (OCEAN SIDE PUBLICATIONS INC, 2008)
Mucosal immunotherapy is suggested as a treatment strategy for tolerance induction in allergic diseases. The purpose of this study was to determine the effect of transferred splenic T cells from intranasal ovalbumin (OVA)-immunized mice to naive mice before sensitization on its impact of cytokine production and airway histopathology. BALB/c mice in group I received intranasal immunotherapy (days1-6), carboxylfluorescein succinyl ester (CFSE)-labeled splenocytes or splenic T cells were i.v. transferred to naive recipients (group 11) before OVA sensitization. Acute murine asthma model was established by two i.p. OVA injections (days 21 and 28) and seven OVA nebulizations (days 42-48) in groups 1, 11 and III. Groups If[ and IV served as asthma model and control, respectively. CFSE-labeled cells in splenocytes and lymph node lymphocytes, lung histopathology, IL-4, IL-10, and interferon (IFN) gamma cytokines of recipients were analyzed 24 hours after OVA nebulization challenge. CFSE-labeled T cells from group I were detected in spleen and regional lymph nodes of the OVA-sensitized recipients (group 11). Smooth muscle and thickness of airways were less in intranasal OVA immunotherapy and OVA-sensitized recipients when compared with the asthma model (p < 0.05). Area of inflammation was significantly suppressed in OVA-sensitized recipients compared with the asthma model (p < 0.01). IL-10 and IFN-gamma levels in splenocyte supernatants were significantly increased in intranasal immunotherapy and OVA-sensitized recipients compared with asthma model and controls (P < 0.01). IL-4 levels were significantly less in intranasal immunotherapy group and the OVA-sensitized recipient group when compared with asthma the model group (p < 0.05). This study suggests that intranasal immunotherapy with allergens regulates T-cell responses and ameliorates airway histopathology in sensitized mice, hence, encouraging mucosal tolerance induction as a suitable treatment of allergic diseases.
Keywords: allergy; IFN-gamma; IL-10; intranasal immunotherapy; mucosal immunotherapy; murine; ovalbumin; T-helper cells; TH1 cells; TH2 cells; MUCOSAL TOLERANCE INDUCTION; AIRWAY HYPERRESPONSIVENESS; SUBLINGUAL IMMUNOTHERAPY; IN-VIVO; INFLAMMATION; HYPERREACTIVITY; INTERLEUKIN-10; MECHANISMS; CHALLENGE; ASTHMA